Microfluidic technology and simulation models in studying pharmacokinetics during pregnancy - Kammala, Ananth K.; Richardson, Lauren S.; Radnaa, Enkhtuya; Han, Arum; Menon, Ramkumar (Frontiers in Pharmacology, 2023)
The alarming global rate of preterm birth ( 12% of all pregnancies) and increasing maternal and neonatal mortality rates warrant better strategies for safe, reliable, and faster testing of therapeutic compounds for intervention during pregnancy. Current 2D or 3D cell models and/or animal models are insufficient to generate data that can translate into clinical trials. Hence, pregnant women remain "therapeutic orphans" as they are excluded from most drug development considerations and clinical trials. To overcome this limitation, this study utilized recent advances in silico simulation modeling and microfluidic-based organ-on-a-chip platforms to assess their utility in testing potential interventional agents. A multi-organ feto-maternal interface (fetal membrane-decidua-placenta) on-chip (FMi-PLA-OOC), with seven different cell types connected through microchannels to maintain intercellular interactions, was used to investigate drug pharmacokinetics. A model drug (pravastatin) that effectively reduces oxidative stress and inflammation, currently in clinical trials during pregnancy, was tested for its transfer rate across both FMis. Data were compared with reported data from in vivo animal models and ex vivo placenta perfusion models. Pravastatin pharmacokinetics was predicted in pregnant subjects derived from validated nonpregnant drug data using mechanistically based simulation software (Gastroplus®). We report that pravastatin transfer across the FMi-PLA-OOC and predicted pharmacokinetics in in silico models were similar ( 18%). In contrast, animal models yielded supraphysiologic accumulation of drugs in the amniotic fluid ( 33%). In conclusion, FMi-PLA-OOC and in silico models can serve as alternative methods for drug pharmacokinetics, offering valuable insights into drug transport and metabolism across the placenta and fetal membranes during pregnancy.